De novo biosynthesis of quercetin in Yarrowia Lipolytica through systematic metabolic engineering for enhanced yield - Yuxing Dong; Wenping Wei; Mengfan Li; Tao Qian; Jiayun Xu; Xiaohe Chu; Bang-Ce Ye (Bioresources and Bioprocessing)
Abstract Kaempferol and quercetin possess various biological activities, making them valuable in food and medicine. However, their production via traditional methods is often inefficient. This study aims to address this gap by engineering the yeast Yarrowia lipolytica to achieve high yields of these flavonoids. We designed a kaempferol biosynthetic pathway by integrating multiple-copy fusion enzyme expression modules, F3H-(GGGGS)2-FLS, into the genome with an optimized linker (GGGGS)2 to enhance kaempferol production from naringenin. To synthesize quercetin de novo, we introduced the FMOCPR gene into the kaempferol-synthesizing strain using the optimized pFBAin promoter. Notably, increasing glucose concentration effectively boosted the production of both flavonoids. Our results demonstrated kaempferol and quercetin titers reaching 194.30 ± 7.69 and 278.92 ± 11.58 mg/L, respectively, in shake-flask cultures. These findings suggest that Y. lipolytica is a promising platform for the efficient production of flavonoid-derived products.